Boosting biotribological and biological properties of carbon fiber composites by grafting SiC nanowires and hydroxyapatite for hip joint application. Issue 13 (1st July 2022) - Zhao, Fei; Zhang, Leilei; Wang, Jing; Guo, Yao; Sheng, Hongchao; Dong, Zhijie; Mikhalovsky, Sergey V.
Abstract: Carbon fiber composites have great potential application in hip joints, where excellent biotribological and biological properties are required. In this work, SiC nanowires (SiCnws) and hydroxyapatite (HA) were grafted into carbon fiber composites by carbothermal reduction and electrochemical deposition method to obtain carbon fiber-SiCnws-hydroxyapatite-carbon composites (CHS). Results show that SiCnws are grown on the surface of carbon fibers and fill the gaps between carbon fibers. Particle-shaped HA covers both carbon fibers and SiCnws completely. The introduction of SiCnws improves the biotribological properties of CHS. Compared with carbon fiber-hydroxyapatite-carbon composites without SiCnws, the friction coefficient of CHS increased from 0.196 to 0.269, while the wear rate decreased from 0.032 × 10 −14  m 3 /(N·m) to 0.016 × 10 −14  m 3 /(N·m). Biological tests show that CHS could promote cell proliferation and differentiation effectively. With these improved biotribological and biological properties, synthesized CHS composites exhibits a potential to be used as hip joints.